The Effect of Green Product Attributes, Green Trust, and Environmental Awareness on Purchase Intention to Buy Greenwash Detergent - Simangunsong, Ferdinan Sandro; Nuvriasari, Audita (LifeSciFi, 2026)
Environmental concerns arising from the use of household products, especially conventional detergents that are not easily biodegradable, have driven the emergence of eco-friendly detergents as a more sustainable option. In response, this study seeks to examine how green product attributes, green trust, and environmental awareness influence green purchase intention toward Greenwash detergent. The research adopted a quantitative design using a survey approach. The study involved 100 respondents who were already familiar with information about the Greenwash detergent product. Participants were selected through purposive sampling based on criteria relevant to the research objectives. Primary data were gathered using questionnaires measured on a Likert scale and processed through multiple linear regression analysis, following tests of validity, reliability, and classical assumptions. The findings reveal that green product attributes, green trust, and environmental awareness each have a positive and significant partial effect on green purchase intention. Environmentally friendly product characteristics, stronger consumer confidence in the company’s environmental claims, and higher awareness of environmental protection are key factors that encourage the intention to purchase eco-friendly detergent products.